Simulasi Cell Breathing CDMA 2000 1x Menggunakan DELPHI - Hikmaturokhman, Alfin; Susilawati, Hesti; Perdana, Ilham (Jurnal Semesta Teknika, 2007)
Cell breathing is variation of CDMA cell size depends upon the amount of traffic occurs within the cell. This work assume that the cell is in the ideal condition based onÂ the following assumptions,Â each cell is completely isolated from the other cells, with the result that no intercell interference and signals from MS cause no interference within the cell. It makes no intracell interference occurs within the cell. In an ideal condition where is none of interference occurs, cell size and amount of users in a cell depend on several factors such as bitrate, required signal strength that MS must deliver to BS, voice activity factor, power control accuracy factor and Eb/It of the system. The result obtained by change the values of the parameters and based on the result obtained, the impact of the parameter to the cell size and amount of user in a cell could be recognized.